Capital gains, total returns and saving rates - Michael Hudson (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
To focus on the dynamics of how financial wealth is created, obtained, and valued, this paper (1) distinguishes capital gains from income by measuring total returns, and (2) contrasts the capitalized value of rentier income (rent extraction rights and privileges from land, natural resources, and monopolies) from that of industrial profits on tangible capital investment.
Keywords: B40; E2; 330; national income accounting; saving; capital gains